Method for producing multilayer coating film, and multilayer coating film

By applying a glossy pigment dispersion of aluminum thin fragments and titanium oxide and a transparent coating containing hydroxyacrylic resin on the upper layer of the electrodeposition coating film, the problem of insufficient brightness changes and repairability in the prior art was solved, and the problem of low light to shadow brightness in the prior art was realized. A white metal-like coating with high gloss and brightness.

CN119136920APending Publication Date: 2024-12-13KANSAI PAINT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037647.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-13
Filing Date
2023-05-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to maintain high brightness in highlights to shaded areas and provide a white metal-like coating film, while there is a problem of impaired brightness and insufficient repairability of the glossy coating film.

Method used

Using an electrodeposited coating film as the substrate, combining aluminum thin fragment pigment and titanium oxide bright pigment dispersion, a transparent coating containing hydroxyacrylic resin and polyisocyanate compound is formed, and a multi-layer is realized during the heating and curing process. Curing of the coating.

Benefits of technology

It achieves high gloss and high brightness continuity, with high overall brightness from highlights to shaded areas, and has good repairability, meeting the texture requirements of white metal-like coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111744030000121
    Figure BDA0005111744030000121
  • Figure BDA0005111744030000141
    Figure BDA0005111744030000141
  • Figure BDA0005111744030000171
    Figure BDA0005111744030000171
Patent Text Reader

Abstract

The present invention relates to a method for producing a multilayer coating film in which an electrodeposited coating film is sequentially coated with a base coating material, a glitter pigment dispersion containing an aluminum fragment pigment, titanium oxide, a hydroxyl group-containing acrylic resin, a viscosity modifier, and water, and a two-pack clear coating material, and the three layers of coating films are simultaneously cured, and the glitter pigment dispersion contains an aluminum fragment pigment, titanium oxide, a hydroxyl group-containing acrylic resin, a viscosity modifier, and water. The content of titanium oxide is 10% by mass to 20% by mass based on the total solid content of the brilliant pigment dispersion, and the mass ratio of aluminum flake pigment / titanium oxide is 0.8 to 1.2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a multi-layer coating film and a multi-layer coating film. Background Art

[0002] The purpose of coating is mainly to protect materials and give excellent appearance. For industrial products, excellent appearance, especially "texture" is important from the perspective of enhancing their product capabilities. The texture of industrial products expected by consumers is diverse, and recently, a metal-like gloss (hereinafter referred to as "metallic gloss") is expected in the fields of automobile housings, automobile components, household appliances, etc.

[0003] Metallic luster is a texture with the following characteristics: the surface is free of grain, a mirror-like surface, and when further viewed in a direction almost perpendicular to the coated plate, the coated plate appears shiny (highlight). In this texture, the white metal texture requires the highlight area to have high brightness, while the (shadow) area when the coating film is viewed at an angle has a lower brightness than the highlight area, but has a perceptible white color.

[0004] In Patent Document 1, as a method for forming a laminated coating film that can achieve a metallic appearance of a metal-plated surface without the need for electroplating treatment, a method for manufacturing a laminated coating film that exhibits a metallic appearance is disclosed, the method comprising: applying a metallic-like paint to a coated object, the metallic-like paint containing an opaque flaky pigment and a bright pigment obtained by crushing a vapor-deposited metal film into metal flakes; and applying a transparent top coating paint to the formed metallic coating film layer.

[0005] Patent document 2 discloses a method for producing a bright coating film, which is capable of obtaining a coating film that does not reduce the brightness of aluminum thin flake pigments, does not darken when the coating film is observed at an angle (shadow portion), and displays a bright white color. The method comprises forming a bright base coating film containing aluminum thin flake pigments in a specific shape on a substrate, forming a first clear coating film containing organic resin particles on the above-mentioned bright base coating film, and further forming a second clear coating film on the first clear coating film.

[0006] In Patent Document 3, a coating film manufacturing method is disclosed as a coating film having high whiteness, a refined appearance, and a relatively smooth brightness change from highlights (near specular reflected light) to shadows (in an inclined direction) giving a sense of calmness. The method comprises sequentially forming a colored base coating film, a metal base coating film, and an upper transparent coating film, wherein the brightness L* of the colored base coating film in the L*a*b* colorimetric system is 75 to 90, and the metal base coating film contains four types of optical interference pigments having different interference colors in highlights.

[0007] Patent Document 4 discloses a method for producing a multilayer coating film having high brightness from highlights to shadows, particularly being able to impart white metallic luster, and having excellent adhesion and water resistance, comprising the following steps (1) to (4): (1) applying a base coating (X) to a coated object to form a base coating film; (2) applying a bright pigment dispersion (Y) to the base coating film formed in step (1) to form a dry film having a thickness of 0.0 (3) applying a clear coating (Z) to the clear coating film formed in step (2) to form a clear coating film; and (4) simultaneously curing the uncured base coating film, the uncured clear coating film and the uncured clear coating film formed in steps (1) to (3), wherein the clear pigment dispersion (Y) comprises aluminum flake pigment (A), light scattering particles (B), a hydroxyl-containing acrylic resin (C) and water.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2004-8931

[0011] Patent Document 2: Japanese Patent Application Publication No. 2003-245603

[0012] Patent Document 3: Japanese Patent Application Publication No. 2011-45805

[0013] Patent Document 4: WO2019 / 065961 Summary of the invention

[0014] Problems to be solved by the invention

[0015] In the technology described in Patent Document 1, the concentration of flaky pigments and bright pigments in a metallic-like paint is increased so that the flaky pigments and bright pigments are oriented parallel to the coating surface, thereby forming a metallic-like coating film, however, the brightness changes greatly from highlights to shadows, and the shadows become darker, making it impossible to obtain a white metallic-like coating film.

[0016] According to the method described in Patent Document 2, a coating film containing organic resin particles is laminated on a bright coating film containing aluminum flake pigments, thereby obtaining a bright coating film that does not darken when the coating film is observed at an angle (shadow portion) and displays a bright white color. However, there is a problem that the organic resin particles scatter incident light, resulting in a loss of brightness of the bright coating film.

[0017] According to the method described in Patent Document 3, due to the presence of a plurality of types of optical interference pigments having different interference colors, a delicate white pearl coating color can be obtained, however, the use of an optical interference plate results in insufficient brightness of highlights and a large change in brightness from highlights to shadows, making it impossible to obtain the above-mentioned white metallic-like coating film.

[0018] The multilayer coating formed by the method described in Patent Document 4 has an excellent "texture", however, when transferring to the next step in the coating process, dust may adhere to the surface of the coating during the heating and curing process of the coating, and dents may appear on the coating, thereby reducing the design quality, so good repairability is also required.

[0019] The object of the present invention is to provide a white metal-like multilayer coating film having high gloss at highlights, high overall brightness from highlights to shadows, and good repairability, and a method for manufacturing the same.

[0020] Means for solving problems

[0021] The present invention covers the subject matter described in the following items.

[0022] Item 1. A method for producing a multilayer coating film, the method comprising the following steps (1) to (4):

[0023] (1) directly applying the base coating (X) to the electrodeposition coating film to form a base coating film having a dry film thickness of 20 μm to 35 μm and a brightness L*45 of 85 to 95;

[0024] (2) applying the bright pigment dispersion (Y) to the base coating film formed in step (1) to form a bright coating film having a dry film thickness of 0.01 μm to 1.0 μm;

[0025] (3) applying a two-component clear coating (Z) containing a hydroxyl group-containing acrylic resin and a polyisocyanate compound to the bright coating film formed in step (2) to form a clear coating film; and

[0026] (4) by heating the uncured base coating film, the uncured bright coating film and the uncured clear coating film formed in the steps (1) to (3), so that the three coating films are cured simultaneously, wherein:

[0027] The bright pigment dispersion (Y) contains aluminum flake pigment (A), titanium oxide (B), hydroxyl-containing acrylic resin (C), viscosity modifier (D) and water.

[0028] The content of titanium oxide (B) is 10% to 20% by mass in the total solid content of the bright pigment dispersion (Y).

[0029] The mixing ratio of the aluminum flake pigment (A) and the titanium oxide (B) is 0.8 to 1.2 in terms of the mass ratio of the aluminum flake pigment (A) / titanium oxide (B).

[0030] The multilayer coating film has a brightness L*45 in the range of 75 to 85, a 60 degree specular gloss in the range of 95 to 105, and a color flop value in the range of 0.5 to 0.7.

[0031] Item 2. A multilayer coating film, which comprises an electrodeposition coating film, a base coating film, a bright coating film and a clear coating film in sequence,

[0032] The base coating film has a thickness of 20 μm to 35 μm, a brightness L*45 of 85 to 95,

[0033] The bright coating film contains aluminum flake pigment (A) and titanium oxide (B) and has a film thickness of 0.01 μm to 1.0 μm.

[0034] The content of titanium oxide (B) in the bright coating film is 10% to 20% by mass, and the mass ratio of aluminum flake pigment (A) to titanium oxide (B) is 0.8 to 1.2.

[0035] The transparent coating film comprises a cured product of a hydroxyl-containing acrylic resin and a polyisocyanate compound.

[0036] The multi-layer coating film has a brightness L*45 in the range of 75 to 85, a 60-degree specular gloss in the range of 95 to 105, and a color flop value in the range of 0.5 to 0.7.

[0037] Effects of the Invention

[0038] The present invention can provide a multi-layer coating film having a white metallic texture with high gloss at highlights, high overall brightness from highlights to shadows, and good repairability, and a method for manufacturing the same. DETAILED DESCRIPTION

[0039] <Method for producing multilayer coating film>

[0040] The method for producing a multilayer coating film of the present invention comprises the following steps (1) to (4):

[0041] (1) directly applying the base coating (X) to the electrodeposition coating film to form a base coating film having a dry film thickness of 20 μm to 35 μm and a brightness L*45 of 85 to 95;

[0042] (2) applying the bright pigment dispersion (Y) to the base coating film formed in step (1) to form a bright coating film having a dry film thickness of 0.01 μm to 1.0 μm;

[0043] (3) applying a two-component clear coating (Z) containing a hydroxyl group-containing acrylic resin and a polyisocyanate compound to the bright coating film formed in step (2) to form a clear coating film; and

[0044] (4) by heating the uncured base coating film, the uncured bright coating film and the uncured clear coating film formed in the steps (1) to (3), so that the three coating films are cured simultaneously, wherein:

[0045] The bright pigment dispersion (Y) contains aluminum flake pigment (A), titanium oxide (B), hydroxyl-containing acrylic resin (C), viscosity modifier (D) and water.

[0046] The content of titanium oxide (B) is 10% to 20% by mass in the total solid content of the bright pigment dispersion (Y).

[0047] The mixing ratio of the aluminum flake pigment (A) and the titanium oxide (B) is 0.8 to 1.2 in terms of the mass ratio of the aluminum flake pigment (A) / titanium oxide (B).

[0048] The multi-layer coating film has a brightness L*45 in the range of 75 to 85, a 60-degree specular gloss in the range of 95 to 105, and a color flop value in the range of 0.5 to 0.7.

[0049] [Process (1)]

[0050] Step (1) of the present invention is a step of directly applying the base coating material (X) to the electrodeposition coating film to form a base coating film having a dry film thickness of 20 to 35 μm and a brightness L*45 of 85 to 95.

[0051] Electrodeposition coating

[0052] According to the method for producing a multilayer coating film of the present invention, first, an electrodeposition coating material is applied to a coating object such as a steel plate, and the electrodeposition coating material is heated and cured to form an electrodeposition coating film.

[0053] As the steel sheet, there can be used a steel sheet for automobile bodies, such as alloyed hot-dip galvanized steel sheet, hot-dip galvanized steel sheet, electrogalvanized steel sheet, cold-rolled steel sheet, etc. The steel sheet may be a steel sheet subjected to surface treatment such as phosphate treatment, chromate treatment, composite oxide treatment, etc.

[0054] Furthermore, as the above-mentioned electrodeposition paint, any known electrodeposition paint can be used, for example, an electrodeposition paint described in Japanese Patent Laid-Open No. 2003-306796 and the like can be used, and a cationic electrodeposition paint can be particularly preferably used.

[0055] Base coating (X)

[0056] The base coating film can be formed by applying the base coating material (X) to the above-mentioned electrodeposition coating film.

[0057] The dry film thickness of the base coating film is 20 to 35 μm, preferably 23 to 31 μm, from the viewpoint of primer hiding property and finish.

[0058] Furthermore, the brightness L*45 of the base coating film is 85 to 95, preferably 87 to 92, from the viewpoint of forming a multilayer coating film having a white metallic texture with high gloss in highlights and high overall brightness from highlights to shadows.

[0059] Here, specifically, brightness L*45 refers to brightness L* in the L*a*b* colorimetric system calculated from the spectral reflectance of light irradiated at an angle of 45 degrees to the coating film and received at an angle of 45 degrees to the specular reflected light. Specifically, it can be defined as a value measured using a multi-angle spectrophotometer "MA-68II" (trade name, manufactured by Videojet X-Rite Corporation).

[0060] As the base coating material (X), there can be specifically used a known thermosetting coating material containing a vehicle-forming resin, a pigment, and a solvent such as an organic solvent and / or water as main components.

[0061] The developer-forming resin used in the base coating (X) may be a thermosetting resin, a room temperature curable resin, etc. From the viewpoint of water resistance, chemical resistance, weather resistance, etc., a thermosetting resin is preferably used. The developer-forming resin is preferably used in combination with a base resin and a crosslinking agent.

[0062] The matrix resin is preferably a resin having excellent weather resistance, transparency, etc. Specifically, acrylic resin, polyester resin, epoxy resin, polyurethane resin, etc. may be mentioned.

[0063] Examples of the acrylic resin include resins obtained by copolymerizing an α,β-ethylenically unsaturated carboxylic acid, a (meth)acrylate having a functional group such as a hydroxyl group, an amide group or a methylol group, other (meth)acrylates, styrene and the like.

[0064] As the polyester resin, there can be used polyester resins obtained by condensation reaction of polyols such as ethylene glycol, propylene glycol, butanediol, 1,6-hexanediol, trimethylolpropane and pentaerythritol with polycarboxylic acid components such as adipic acid, isophthalic acid, terephthalic acid, phthalic anhydride, hexahydrophthalic anhydride and trimellitic anhydride.

[0065] Examples of epoxy resins include epoxy ester resins, which are obtained by synthesizing epoxy esters by reacting epoxy groups with unsaturated fatty acids and adding α,β-unsaturated acids to the unsaturated groups, or by esterifying the hydroxyl groups of epoxy esters with polybasic acids such as phthalic acid or trimellitic acid.

[0066] Examples of the polyurethane resin include polyurethane resins obtained by reacting the above-mentioned acrylic resin, polyester resin or epoxy resin with a diisocyanate compound to increase the molecular weight.

[0067] Base coating (X) can be any one of water-based coating or solvent-based coating, but from the viewpoint of reducing the VOC of coating, preferably water-based coating. When base coating (X) is water-based coating, it is possible to use a matrix resin containing a hydrophilic group, and neutralize the hydrophilic group to form an alkali salt, so as to be soluble in water or dispersed in water, the hydrophilic group is, for example, carboxyl, hydroxyl, methylol, amino, sulfonic acid group or polyoxyethylene, etc., most usually carboxyl, and the amount of the hydrophilic group is enough to make the resin soluble in water or dispersed in water. The amount of the hydrophilic group (for example, carboxyl) used in this case is not particularly limited, and can be arbitrarily selected according to water solubility or water dispersibility. The amount of the hydrophilic group usually makes the acid value be about 10mgKOH / g or larger, and is preferably 30mgKOH / g to 200mgKOH / g. In addition, as the alkaline substance for neutralization, sodium hydroxide, amine compounds, etc. can be listed.

[0068] In addition, the above-mentioned monomer components may be subjected to emulsion polymerization in the presence of a surfactant and a water-soluble resin, thereby dispersing the above-mentioned resin in water. Further, an aqueous dispersion may be obtained by, for example, dispersing the above-mentioned resin in water in the presence of an emulsifier, etc. In the aqueous dispersion, the base resin may not contain the above hydrophilic group at all, or may contain the above hydrophilic group in an amount less than the amount of the hydrophilic group in the water-soluble resin.

[0069] The crosslinking agent is used to crosslink and cure the above-mentioned base resin by heating. For example, amino resins, polyisocyanate compounds, blocked polyisocyanate compounds, epoxy-containing compounds, carboxyl-containing compounds, carbodiimide-containing compounds, hydrazide-containing compounds, and semicarbazide-containing compounds can be listed. Among them, amino resins, polyisocyanate compounds, blocked polyisocyanate compounds, and carbodiimide-containing compounds that can react with hydroxyl groups are preferred. These crosslinking agents can be used alone or in combination of two or more.

[0070] Specifically, amino resins obtained by condensing or co-condensing melamine, benzoguanamine, urea, etc. with formaldehyde, or further etherifying with a lower monohydric alcohol, can be used well. In addition, polyisocyanate compounds or blocked polyisocyanate compounds can also be used appropriately.

[0071] The proportion of each component in the base coating material (X) can be arbitrarily selected as required. From the viewpoint of water resistance, finish, etc., it is generally preferred that the proportion of the base resin is 60% to 90% by mass, and particularly 70% to 85% by mass, and the proportion of the crosslinking agent is 10% to 40% by mass, and particularly 15% to 30% by mass, based on the total mass of the two components.

[0072] The pigment imparts color and bottom hiding property to the base coating film formed by the base coating (X). By adjusting the type and the amount of the pigment, the brightness L*45 value of the coating film obtained by the base coating (X) can be adjusted. As the pigment, metallic pigments, rust-proof pigments, coloring pigments, body pigments, etc. can be listed. Among them, coloring pigments are preferably used, and from the viewpoints of imparting white metal textures to the multilayer coating film, titanium oxide pigments are further preferably used.

[0073] In the base coating material (X) of the present invention, coloring pigments other than the titanium oxide pigment may also be used in appropriate combination depending on base hiding property, desired color, and the like.

[0074] The amount of the pigment in the base coating material (X) is preferably 50 to 200 parts by mass, and more preferably 80 to 150 parts by mass, based on 100 parts by mass of the total amount of the base resin and the crosslinking agent.

[0075] The base coating (X) can be applied by a common method. When the base coating (X) is a water-based coating, for example, deionized water and additives selected as needed (such as a thickener and a defoamer) are added to the base coating (X) so that the solid content is adjusted to about 30% by mass to 70% by mass, and the viscosity is adjusted to 500cps / 6rpm to 6000cps / 6rpm (B-type viscometer), and then the resultant is applied to the surface of the object to be coated by spraying, rotary atomization coating, etc. Electrostatic charge can be applied as needed during coating.

[0076] [Step (2)]

[0077] The step (2) of the present invention is a step of applying the bright pigment dispersion (Y) to the base coating film formed in the step (1) to form a bright coating film having a dry film thickness of 0.01 μm to 1.0 μm.

[0078] Bright pigment dispersion (Y)

[0079] A bright pigment dispersion (Y) can be applied to the above-mentioned base coating film to form a bright coating film.

[0080] From the viewpoint of forming a multilayer coating film having a white metallic texture with high gloss in highlights, high overall brightness from highlights to shadows, and good repairability, the dry film thickness of the bright coating film is 0.01 to 1.0 μm, preferably 0.1 to 0.8 μm.

[0081] The bright pigment dispersion (Y) contains an aluminum flake pigment (A), titanium oxide (B), a hydroxyl group-containing acrylic resin (C), a viscosity modifier (D), and water.

[0082] Aluminum flake pigment (A)

[0083] The aluminum flake pigment (A) is produced by pulverizing or grinding aluminum in a ball mill or attritor using a pulverizing aid in the presence of a pulverizing liquid medium. The pulverizing aid used in the production process of the aluminum flake pigment (A) may be a higher fatty acid such as oleic acid, stearic acid, isostearic acid, lauric acid, palmitic acid, and myristic acid, as well as aliphatic amines, aliphatic amides, and aliphatic alcohols. As the pulverizing liquid medium, an aliphatic hydrocarbon such as mineral spirits is used.

[0084] The aluminum flake pigment (A) preferably has an average particle size in the range of 1 μm to 100 μm, more preferably 5 μm to 50 μm, and particularly preferably 7 μm to 30 μm. The thickness is preferably 0.01 μm to 2.0 μm, and particularly preferably 0.02 μm to 1.0 μm.

[0085] From the viewpoint of forming a multilayer coating film having a white metallic texture with high gloss in highlights, high overall brightness from highlights to shadows, and good repairability, the content of the aluminum flake pigment (A) in the bright pigment dispersion (Y) is preferably 1% by mass to 30% by mass, and more preferably 5% by mass to 20% by mass, based on the total solid content of the bright pigment dispersion (Y).

[0086] Titanium oxide (B)

[0087] The content of titanium oxide (B) in the bright pigment dispersion (Y) is 10 to 20% by mass, preferably 12 to 18% by mass, based on the total solid content of the bright pigment dispersion (Y).

[0088] When the content of titanium oxide (B) is within the above range, a multilayer coating film having high gloss in highlights, high overall brightness from highlights to shadows, and good repairability and a white metallic texture can be formed.

[0089] The mixing ratio of the aluminum flake pigment (A) and the titanium oxide (B) in the bright pigment dispersion (Y) is 0.8 to 1.2, preferably 0.85 to 1.15, in terms of the mass ratio of the aluminum flake pigment (A) / titanium oxide (B).

[0090] By setting the mixing ratio of the aluminum flake pigment (A) and the titanium oxide (B) within the above range, a multilayer coating film having a white metallic texture with high gloss in highlights, high overall brightness from highlights to shadows, and good repairability can be formed.

[0091] Hydroxyl-containing acrylic resin (C)

[0092] The hydroxyl-containing acrylic resin (C) is an acrylic resin having at least one hydroxyl group in one molecule. The hydroxyl-containing acrylic resin (C) can be a known water-soluble or water-dispersible hydroxyl-containing acrylic resin used in water-based coatings. The hydroxyl-containing acrylic resin (C) can be produced by copolymerizing a hydroxyl-containing polymerizable unsaturated monomer and other polymerizable unsaturated monomers copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer by a known method such as solution polymerization.

[0093] The hydroxyl-containing polymerizable unsaturated monomer is a compound having one or more hydroxyl groups and one or more polymerizable unsaturated bonds in one molecule. Examples thereof include monoesters of glycols such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and polyethylene glycol mono(meth)acrylate, and acrylic acid or methacrylic acid; and compounds obtained by ring-opening polymerization of ε-caprolactone with monoesters of the above-mentioned polyols and acrylic acid or methacrylic acid.

[0094] Other polymerizable unsaturated monomers copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer can be appropriately selected and used according to the desired properties of the hydroxyl-containing acrylic resin. Specific examples of the monomers are listed below. These can be used alone or in combination of two or more.

[0095] In addition, in this specification, "(meth)acrylate" means acrylate or methacrylate. "(meth)acrylic acid" means acrylic acid or methacrylic acid. In addition, "(meth)acryl" means acrylyl or methacryl. In addition, "(meth)acrylamide" means acrylamide or methacrylamide.

[0096] (i) Alkyl (meth)acrylate or cycloalkyl (meth)acrylate: for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, tridecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, tricyclodecyl (meth)acrylate, etc.

[0097] (ii) Polymerizable unsaturated monomer having an isobornyl group: isobornyl (meth)acrylate, etc.

[0098] (iii) Polymerizable unsaturated monomer having an adamantyl group: adamantyl (meth)acrylate, etc.

[0099] (iv) Polymerizable unsaturated monomer having a tricyclodecenyl group: tricyclodecenyl (meth)acrylate, etc.

[0100] (v) Aromatic ring-containing polymerizable unsaturated monomers: benzyl (meth)acrylate, styrene, α-methylstyrene, vinyltoluene, etc.

[0101] (vi) Polymerizable unsaturated monomers having an alkoxysilyl group: vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-(meth)acryloxypropyltrimethoxysilane, γ-(meth)acryloxypropyltriethoxysilane, and the like.

[0102] (vii) Polymerizable unsaturated monomers having a fluorinated alkyl group: perfluoroalkyl (meth)acrylates such as perfluorobutyl ethyl (meth)acrylate and perfluorooctyl ethyl (meth)acrylate; fluoroolefins, and the like.

[0103] (viii) A polymerizable unsaturated monomer having a photopolymerizable functional group such as a maleimide group.

[0104] (ix) Vinyl compounds: N-vinyl pyrrolidone, ethylene, butadiene, chloroprene, vinyl propionate, vinyl acetate, and the like.

[0105] (x) Carboxyl group-containing polymerizable unsaturated monomers: (meth)acrylic acid, maleic acid, crotonic acid, β-carboxyethyl acrylate, etc.

[0106] (xi) Nitrogen-containing polymerizable unsaturated monomers: (meth)acrylonitrile, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, methylenebis(meth)acrylamide, ethylenebis(meth)acrylamide, adducts of glycidyl (meth)acrylate and amines, etc.

[0107] (xii) A polymerizable unsaturated monomer having at least two polymerizable unsaturated groups in one molecule: allyl (meth)acrylate, ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol (meth)acrylate, etc.

[0108] (xiii) Epoxy-containing polymerizable unsaturated monomers: glycidyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, allyl glycidyl ether, etc.

[0109] (xiv) (meth)acrylates having a polyoxyethylene chain having an alkoxy group at a molecular terminal.

[0110] (xv) Polymerizable unsaturated monomers having a sulfonic acid group: 2-acrylamide-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, allylsulfonic acid, 4-styrenesulfonic acid, etc.; sodium salts and ammonium salts of these sulfonic acids, etc.

[0111] (xvi) Polymerizable unsaturated monomers having a phosphoric acid group: acid phosphonooxyethyl (meth)acrylate, acid phosphonooxypropyl (meth)acrylate, acid phosphonooxypoly (oxyethylene) glycol (meth)acrylate, acid phosphonooxypoly (oxypropylene) glycol (meth)acrylate, and the like.

[0112] (xvii) Polymerizable unsaturated monomers having ultraviolet absorbing functional groups: 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2-hydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, etc.

[0113] (xviii) Light-stable polymerizable unsaturated monomers: 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine, 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 4-crotonyloxy-2,2,6,6-tetramethylpiperidine, 4-crotonylamino-2,2,6,6-tetramethylpiperidine, 1-crotonyl-4-crotonyloxy-2,2,6,6-tetramethylpiperidine, and the like.

[0114] (xix) Polymerizable unsaturated monomers having a carbonyl group: acrolein, diacetone acrylamide, diacetone methacrylamide, acetoacetoxyethyl methacrylate, formylstyrene, vinyl alkyl ketones having 4 to 7 carbon atoms (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl butyl ketone), and the like.

[0115] (xx) Polymerizable unsaturated monomers having an acid anhydride group: maleic anhydride, itaconic anhydride, citraconic anhydride, and the like.

[0116] The hydroxyl value of the hydroxyl-containing acrylic resin (C) is preferably 10 mgKOH / g to 150 mgKOH / g, more preferably 50 mgKOH / g to 100 mgKOH / g. The acid value is preferably 150 mgKOH / g or less, more preferably 145 mgKOH / g or less. The weight average molecular weight is preferably 1,000 to 100,000, more preferably 2,000 to 60,000.

[0117] In addition, in this specification, the weight average molecular weight of the hydroxyl-containing acrylic resin (C) is a value obtained by converting the retention time (retention capacity) measured using gel permeation chromatography (GPC) into the molecular weight of polystyrene based on the retention time (retention capacity) of a standard polystyrene with a known molecular weight measured under the same conditions. Specifically, it can be measured under the following conditions: the gel permeation chromatography apparatus uses "HLC-8120GPC" (trade name, manufactured by Tosoh Corporation), the chromatographic columns use "TSKgel G4000HXL", "TSKgel G3000HXL", "TSKgel G2500HXL" and "TSKgel G2000HXL" (trade names, all manufactured by Tosoh Corporation) in total four, the detector is a differential refractometer, the mobile phase is tetrahydrofuran, the measurement temperature is 40°C, and the flow rate is 1 mL / min.

[0118] From the viewpoint of forming a multilayer coating film having a white metallic texture with high gloss in highlights, high overall brightness from highlights to shadows, and good repairability, the content of the hydroxyl-containing acrylic resin (C) in the bright pigment dispersion (Y) is preferably 0.5% by mass to 10% by mass, and more preferably 1% by mass to 5% by mass, based on the total solid content of the bright pigment dispersion (Y).

[0119] Viscosity modifier (D)

[0120] As the viscosity modifier (D) in the bright pigment dispersion (Y), a known viscosity modifier can be used. Examples thereof include fine silica powder, mineral viscosity modifiers, barium sulfate micronized powder, polyamide viscosity modifiers, organic resin microparticle viscosity modifiers, diurea viscosity modifiers, urethane associative viscosity modifiers, acrylic acid swelling type polyacrylic acid viscosity modifiers, cellulose viscosity modifiers, etc. Among them, in terms of obtaining a coating film with excellent metallic luster, it is particularly preferable to use a mineral viscosity modifier, a polyacrylic acid viscosity modifier, or a cellulose viscosity modifier.

[0121] As mineral viscosity modifiers, swellable layered silicates having a 2:1 type crystal structure can be cited. Specifically, montmorillonite clay minerals, such as natural or synthetic montmorillonite, saponite, hectorite, stevensite, beidellite, nontronite, bentonite and laponite; swellable mica clay minerals, such as Na-type tetrasilicon fluoride mica, Li-type tetrasilicon fluoride mica, Na-salt-type fluoride mica and Li-type fluoride mica; and vermiculite; or their substitutes and derivatives, or mixtures thereof.

[0122] Examples of the polyacrylic acid-based viscosity modifier include sodium polyacrylate and polyacrylic acid-(meth)acrylate copolymers.

[0123] Commercial products of polyacrylic acid-based viscosity modifiers include, for example, "Primal ASE-60", "Primal TT615" and "Primal RM5" (trade names) manufactured by The Dow Chemical Company, and "SN Thickener 613", "SN Thickener 618", "SN Thickener 630", "SN Thickener 634" and "SN Thickener 636" (trade names) manufactured by San Nopco. The acid value of the solid content of the polyacrylic acid-based viscosity modifier is in the range of 30 mgKOH / g to 300 mgKOH / g, preferably in the range of 80 mgKOH / g to 280 mgKOH / g.

[0124] Examples of the cellulose-based viscosity modifier include carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and cellulose nanofiber gel.

[0125] These viscosity modifiers can be used alone or in combination of two or more.

[0126] From the viewpoint of forming a multilayer coating film having high gloss at highlights, the content of the viscosity modifier (D) in the bright pigment dispersion (Y) is preferably 5% by mass to 30% by mass, more preferably 10% by mass to 25% by mass, based on the total solid content of the bright pigment dispersion (Y).

[0127] Other components

[0128] The bright pigment dispersion (Y) may further contain, as necessary, a resin other than the hydroxyl-containing acrylic resin (C), an organic solvent, a pigment dispersant, an anti-settling agent, a defoaming agent, an ultraviolet absorber, a surface conditioner, and the like.

[0129] Examples of resins other than the hydroxyl-containing acrylic resin (C) include acrylic resins not containing hydroxyl groups, polyester resins which may contain hydroxyl groups, alkyd resins which may contain hydroxyl groups, polyurethane resins which may contain hydroxyl groups, etc. Among them, hydroxyl-containing polyester resins are preferred.

[0130] When the bright pigment dispersion (Y) contains a hydroxyl-containing polyester resin, the content thereof is preferably 10 to 60% by mass, more preferably 20 to 50% by mass, based on the total solid content of the bright pigment dispersion (Y).

[0131] Coating of bright pigment dispersion (Y)

[0132] The bright pigment dispersion (Y) is prepared by mixing and dispersing the above components. The solid content during coating is adjusted to 0.1% to 7% by mass, and preferably 1% to 5% by mass, based on the bright pigment dispersion (Y).

[0133] Regarding the viscosity of the bright pigment dispersion (Y), the viscosity measured at 20° C. by a B-type viscometer at 60 rpm after 1 minute (also referred to as “B60 value” in this specification) is preferably 30 to 1000 mPa·s. The viscometer used in this case is LVDV-I (trade name, manufactured by Brookfield Company, B-type viscometer).

[0134] The bright pigment dispersion (Y) can be applied by a method such as electrostatic spraying, air spraying or airless spraying. In the method for producing a multi-layer coating film of the present invention, rotary atomization type electrostatic spraying is particularly preferred.

[0135] [Step (3)]

[0136] The step (3) of the present invention is a step of forming a clear coating film by applying a two-component clear coating (Z) containing a hydroxyl group-containing acrylic resin and a polyisocyanate compound to the bright coating film formed in the step (2).

[0137] Two-component clear coating (Z)

[0138] The two-component clear coating material (Z) contains a hydroxyl group-containing acrylic resin and a polyisocyanate compound.

[0139] The hydroxyl-containing acrylic resin can be produced by copolymerizing a hydroxyl-containing polymerizable unsaturated monomer and another polymerizable unsaturated monomer copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer by a known method such as solution polymerization in an organic solvent or emulsion polymerization in water.

[0140] As the hydroxyl group-containing polymerizable unsaturated monomer, the hydroxyl group-containing polymerizable unsaturated monomers described in the description column of the hydroxyl group-containing acrylic resin (C) can be used.

[0141] As other polymerizable unsaturated monomers copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer, those described in the description of the hydroxyl-containing acrylic resin (C) can be used.

[0142] The polyisocyanate compound is a compound having at least two isocyanate groups in one molecule, and examples thereof include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic-aliphatic polyisocyanates, aromatic polyisocyanates, and derivatives of these polyisocyanates.

[0143] Examples of the aliphatic polyisocyanate include aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, 2,6-diisocyanatohexanoic acid Methyl ester (common name: lysine diisocyanate); aliphatic triisocyanates, such as 2-isocyanatoethyl 2,6-diisocyanatohexanoate, 1,6-diisocyanato-3-isocyanatomethylhexane, 1,4,8-triisocyanatooctane, 1,6,11-triisocyanatoundecane, 1,8-diisocyanato-4-isocyanatomethyloctane, 1,3,6-triisocyanatohexane, 2,5,7-trimethyl-1,8-diisocyanato-5-isocyanatomethyloctane; and the like.

[0144] Examples of the alicyclic polyisocyanate include alicyclic diisocyanates such as 1,3-cyclopentene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (common name: isophorone diisocyanate), 4-methyl-1,3-cyclohexylene diisocyanate (common name: hydrogenated TDI), 2-methyl-1,3-cyclohexylene diisocyanate, and 1,3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate. Cyclohexyl diisocyanate, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (common name: hydrogenated xylylene diisocyanate) or a mixture thereof, methylenebis(4,1-cyclohexanediyl)diisocyanate (common name: hydrogenated MDI), norbornane diisocyanate; alicyclic triisocyanates, such as 1,3,5-triisocyanatocyclohexane, 1,3,5-trimethylisocyanatocyclohexane, 2-(3-isocyanatopropyl)isocyanate, 2-(3-isocyanatopropyl)-2,6-bis(isocyanatomethyl)-bicyclo(2.2.1)heptane, 3-(3-isocyanatopropyl)-2,5-bis(isocyanatomethyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 1) heptane, 6-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 6-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane; and the like.

[0145] As the aromatic-aliphatic polyisocyanate, there can be cited, for example, aromatic-aliphatic diisocyanates, such as methylenebis(4,1-phenylene)diisocyanate (common name: MDI), 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene (common name: tetramethylxylylene diisocyanate) or a mixture thereof; aromatic-aliphatic triisocyanates, such as 1,3,5-triisocyanatomethylbenzene; and the like.

[0146] As the aromatic polyisocyanate, there can be mentioned, for example, aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 2,4-toluene diisocyanate (common name: 2,4-TDI) or 2,6-toluene diisocyanate (common name: 2,6-TDI) or a mixture thereof, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate; aromatic triisocyanates such as triphenylmethane-4,4',4"-triisocyanate, 1,3,5-triisocyanatobenzene, 2,4,6-triisocyanatotoluene; aromatic tetraisocyanates such as 4,4'-diphenylmethane-2,2',5,5'-tetraisocyanate; and the like.

[0147] In addition, examples of the polyisocyanate derivatives include dimers and trimers of the above-mentioned polyisocyanates, biuret, allophanate, uretdione, uretimines, isocyanurates, oxadiazinetriones, polymethylene polyphenyl polyisocyanates (crude MDI, polymeric MDI), crude TDI, and the like.

[0148] These polyisocyanates and derivatives thereof may be used alone or in combination of two or more.

[0149] In the present invention, from the viewpoint of curability and scratch resistance of the coating film, the equivalent ratio (OH / NCO) of the hydroxyl group of the hydroxyl-containing acrylic resin to the isocyanate group of the polyisocyanate compound is preferably in the range of 0.5 to 2.0, and more preferably in the range of 0.8 to 1.5.

[0150] The clear coating material (Z) may further contain additives as appropriate, such as a solvent (water, an organic solvent, etc.), a curing catalyst, a defoaming agent, and an ultraviolet absorber.

[0151] The form of the clear coating (Z) is not particularly limited, but is generally used as an organic solvent type coating composition. As the organic solvent used in this case, various organic solvents used for coatings can be used, such as aromatic hydrocarbon or aliphatic hydrocarbon solvents; ester solvents; ketone solvents; ether solvents, etc. The organic solvent used can be used directly as the organic solvent used for preparing the hydroxyl-containing resin, or other organic solvents can be appropriately added.

[0152] The solid content concentration of the clear coating material (Z) is preferably in the range of about 30% by mass to 70% by mass, more preferably in the range of about 40% by mass to 60% by mass.

[0153] The coating method of the clear coating (Z) is not particularly limited, and can include coating methods such as air spraying, airless spraying, rotary atomization coating or curtain coating. In these coating methods, electrostatic charge can be applied as needed. Among them, rotary atomization coating using electrostatic charge is preferred. The coating amount of the clear coating (Z) is usually preferably an amount in which the cured film thickness reaches about 10 μm to 50 μm.

[0154] Furthermore, when the clear coating (Z) is applied, it is preferred that the viscosity of the clear coating (Z) is appropriately adjusted in advance using a solvent such as an organic solvent to a viscosity range suitable for the coating method, for example, in rotary atomization coating using electrostatic charge, it is adjusted to a viscosity range of about 15 seconds to 60 seconds as measured by a No. 4 Ford cup viscometer at 20°C.

[0155] [Step (4)]

[0156] Step (4) of the present invention is a step of simultaneously curing the uncured base coating film, uncured bright coating film and uncured clear coating film formed in steps (1) to (3) by heating the three coating films.

[0157] The heating can be performed in a known manner. For example, a drying furnace such as a hot air furnace, an electric furnace, or an infrared induction heating furnace can be used. The heating temperature is in the range of 70°C to 150°C, preferably in the range of 80°C to 140°C. The heating time is not particularly limited, but is preferably 10 minutes to 40 minutes, preferably 20 minutes to 30 minutes.

[0158] <Multi-layer coating>

[0159] The multilayer coating film formed by the production method of the present invention comprises an electrodeposition coating film, a base coating film, a bright coating film and a clear coating film in order, wherein:

[0160] The base coating film has a thickness of 20 μm to 35 μm, a brightness L*45 of 85 to 95,

[0161] The bright coating film contains aluminum flake pigment (A) and titanium oxide (B) and has a film thickness of 0.01 μm to 1.0 μm.

[0162] The content of titanium oxide (B) in the bright coating film is 10% to 20% by mass, and the mass ratio of aluminum flake pigment (A) to titanium oxide (B) is 0.8 to 1.2.

[0163] The transparent coating film comprises a cured product of a hydroxyl-containing acrylic resin and a polyisocyanate compound.

[0164] The multi-layer coating film has a brightness L*45 in the range of 75 to 85, a 60-degree specular gloss in the range of 95 to 105, and a color flop value in the range of 0.5 to 0.7.

[0165] The multilayer coating film formed by the manufacturing method of the present invention has a brightness L*45 in the range of 75 to 85, a 60-degree specular gloss in the range of 95 to 105, and a color flop value in the range of 0.5 to 0.7, and has good repairability. That is, by the manufacturing method of the present invention, a multilayer coating film with a white metallic texture having high gloss in highlights, high overall brightness from highlights to shadows, and good repairability can be obtained.

[0166] The above-mentioned 60-degree specular glossiness means the ratio of the specular reflection from the object surface to the specular reflection light from the reference surface (glass with a refractive index of 1.567), which is a value defined by JIS-Z8741. Specifically, the luminous flux of a specified opening angle is incident on the measurement sample surface at a specified incident angle, and the luminous flux of a specified opening angle reflected in the specular reflection direction is measured by a light receiver, so this is a value measured using a so-called gloss meter. In this specification, the value measured using a gloss meter (micro-TRI-gloss, manufactured by BYK Chemical) is defined as 60-degree specular gloss (60° gloss).

[0167] The angle-dependent color flop value is a value indicating the magnitude of brightness change according to the observation angle. Specifically, a multi-angle spectrophotometer "MA-68II" (trade name, manufactured by Videojet X-Rite) is used to measure the spectral reflectance of light irradiated on the coating film at an angle of 45 degrees, with respect to the light receiving angle of regular reflection light of 15 degrees and 45 degrees, and the Y value (Y15 and Y45, respectively) in the XYZ color system calculated from the spectral reflectance is calculated, and the value obtained using the following formula is defined as the angle-dependent color flop value.

[0168] FF value = 2×(Y15-Y45) / (Y15+Y45)

[0169] Example

[0170] The present invention will be described in more detail below by way of examples and comparative examples. However, the present invention is not limited to these examples. In addition, "parts" and "%" are based on mass.

[0171] <Production of hydroxyl-containing acrylic resin (C)>

[0172] Production Example 1

[0173] 35 parts of propylene glycol monopropyl ether were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirring device, a reflux condenser, a nitrogen introduction tube and a dripping device, and heated to 85°C, and then, a mixture containing 30 parts of methyl methacrylate, 20 parts of 2-ethylhexyl acrylate, 29 parts of n-butyl acrylate, 15 parts of 2-hydroxyethyl acrylate, 6 parts of acrylic acid, 15 parts of propylene glycol monopropyl ether and 2.3 parts of 2,2'-azobis (2,4-dimethylvaleronitrile) was added thereto over 4 hours. After the addition was completed, the mixture was aged for 1 hour. Subsequently, a mixture containing 10 parts of propylene glycol monopropyl ether and 1 part of 2,2'-azobis (2,4-dimethylvaleronitrile) was added thereto over 1 hour. After the addition was completed, the mixture was aged for 1 hour. 7.4 parts of diethanolamine were also added thereto, thereby obtaining a hydroxyl-containing acrylic resin solution (C-1) having a solid content of 55%. The obtained hydroxyl-containing acrylic resin had an acid value of 47 mgKOH / g, a hydroxyl value of 72 mgKOH / g, and a weight average molecular weight of 58,000.

[0174] <Production of hydroxyl-containing polyester resin (R)>

[0175] Production Example 2

[0176] 109 parts of trimethylolpropane, 141 parts of 1,6-hexanediol, 126 parts of 1,2-cyclohexanedicarboxylic anhydride and 120 parts of adipic acid were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirring device, a reflux condenser, a nitrogen introduction tube and a water separator, heated from 160° C. to 230° C. over 3 hours, and then condensed at 230° C. for 4 hours. Next, in order to introduce a carboxyl group into the obtained condensation reaction product, 38.3 parts of trimellitic anhydride was added to the product, followed by a reaction at 170° C. for 30 minutes, and then the product was diluted with 2-ethyl-1-hexanol, thereby obtaining a hydroxyl-containing polyester resin solution (R-1) having a solid content of 70%. The obtained hydroxyl-containing polyester resin had an acid value of 46 mgKOH / g, a hydroxyl value of 150 mgKOH / g, and a number average molecular weight of 1400.

[0177] <Production of titanium oxide pigment dispersion (P)>

[0178] Production Example 3

[0179] 3.6 parts (2 parts of solid content) of hydroxyl-containing acrylic resin solution (C-1), 15 parts of JR-903 (trade name, rutile titanium dioxide pigment, manufactured by Imperial Chemical Industry) and 15.4 parts of distilled water were placed in a stirring mixing container and uniformly mixed, 2-(dimethylamino)ethanol was further added thereto, and the mixture was adjusted to pH 7.5. The obtained mixture was placed in a 225 ml capacity resin bottle, and then 130 parts of zirconium oxide beads having a diameter of 1.5 mm were added thereto, the bottle was sealed, and the mixture was dispersed for 120 minutes using a vibration type paint conditioner. After dispersion, the obtained dispersion was filtered through a 100 mesh screen to remove the zirconium oxide beads, thereby obtaining a titanium oxide pigment dispersion (P-1) having a solid content of 50%.

[0180] Production Examples 4 to 7

[0181] Titanium oxide pigment dispersions (P-2) to (P-5) were obtained in the same manner as in Production Example 3 except that the formulation shown in Table 1 was used.

[0182] The values ​​in Table 1 () are solid content

[0183]

[0184] <Production of bright pigment dispersion (Y)>

[0185] Production Example 8

[0186] 2425 parts of distilled water, 31.9 parts (15 parts of solid content) of "Alpaste EMERAL EMR-B6360" (trade name, non-leafing aluminum, manufactured by Toyo Aluminum Co., Ltd., average particle size D50: 10.3 μm, thickness: 0.19 μm, aluminum content: 47%, surface treated with silica), 34 parts (17 parts of solid content) of titanium oxide pigment dispersion (P-1), 53.6 parts (15 parts of solid content) of "Acrysol ASE-60" (polyacrylic acid viscosity modifier, manufactured by Dow Chemical Company, solid content: 28%), 250 parts (solid content 5 parts) of "Rheocrysta" (trade name, cellulose viscosity modifier, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., solid content 2%), 57 parts (solid content 40 parts) of hydroxyl-containing polyester resin solution (R-1) and 8 parts (solid content 8 parts) of "BYK348" (trade name, manufactured by BYK, silicone surface modifier, non-volatile matter content: 100% by mass) were mixed and stirred to prepare a bright pigment dispersion (Y-1) having a solid content of 3.5% by mass.

[0187] Production Examples 9 to 16

[0188] Bright pigment dispersions (Y-2) to (Y-9) were obtained in the same manner as in Production Example 8 except that the formulation shown in Table 2 was used.

[0189] In addition, the content of titanium oxide (B) in the total solid content of the glittering dispersion (Y) in Table 2 is the same as the content of titanium oxide (B) in the glittering coating film.

[0190]

[0191] <Production of painted objects>

[0192] A cationic electrodeposition coating "Elecron GT-10" (trade name, manufactured by Kansai Paint Co., Ltd., using a blocked polyisocyanate compound as a crosslinking agent in an epoxy resin polyamine cationic resin) was applied by electrodeposition to a degreased and zinc phosphate treated steel plate (JIS G3141, size 400 mm × 300 mm × 0.8 mm) until the film thickness of the cured coating reached 20 μm, and the obtained film was heated at 170° C. for 20 minutes to crosslink and cure to form an electrodeposition coating film, thereby obtaining a coated object.

[0193] <Preparation of test board>

[0194] Example 1

[0195] Step (1): Using a rotary atomizing bell-shaped coating equipment, the base coating (X-1) "WP-580Z N-9.0" (trade name, manufactured by Kansai Paint Co., Ltd., polyester resin water-based mid-coat coating, the L*45 value of the obtained coating film is 90) is applied to the coated object by electrostatic coating until the cured film thickness reaches 27 μm, and the obtained film is allowed to stand for 3 minutes to form a base coating film.

[0196] Step (2): Next, the bright pigment dispersion (Y-1) prepared as described above was applied to the base coating film using a robot bell manufactured by ABB under the conditions of a coating room temperature of 23°C and a humidity of 68% until the dry coating thickness reached 0.5 μm. After standing for 3 minutes, it was preheated at 80°C for 3 minutes to form a bright coating film.

[0197] Step (3): Next, a robot bell manufactured by ABB is used to apply a clear coating (Z-1) "KINO6510" (trade name, manufactured by Kansai Paint Co., Ltd., a hydroxyl / isocyanate-curable acrylic resin / polyurethane resin two-component organic solvent-based coating) to the glossy coating film until the dry coating film thickness reaches 30 μm, thereby forming a clear coating film.

[0198] Step (4): Next, the multilayer coating film was dried by heating at 140° C. for 30 minutes in a hot air circulation drying oven after being left to stand at room temperature for 7 minutes, thereby obtaining a test plate.

[0199] Here, the film thickness of the dried coating film was calculated by the following formula: The same manner applies to the following examples.

[0200] x=(sc*10000) / (S*sg)

[0201] x: Film thickness [μm]

[0202] sc: coating solid content [g]

[0203] S: Evaluation area of ​​coating solid content [cm 2 ]

[0204] sg: coating specific gravity [g / cm 3 ].

[0205] Examples 2 to 9, Comparative Examples 1 to 8

[0206] Except for using the coating material and film thickness shown in Table 3 or Table 4, the same procedure as in Example 1 was carried out to obtain a test plate.

[0207] In addition, the base coating material (X-2) in the table is as follows.

[0208] (X-2): "WP-522H N-8.0" (trade name, manufactured by Kansai Paint Co., Ltd., polyester resin-based water-based mid-coat paint, the obtained coating film has an L*45 value of 80).

[0209] <Evaluation of coating film>

[0210] The coating films of the respective test plates obtained as described above were evaluated in the following manner. Tables 3 and 4 show the results.

[0211] <Brightness L*45>

[0212] A numerical value calculated from the spectral reflectance measured using a multi-angle spectrophotometer “MA-68II” (trade name, manufactured by Videojet X-Rite Corporation) was used.

[0213] <60° mirror gloss>

[0214] The gloss meter "micro-TRI-gloss" (trade name, manufactured by BYK Chemical Co., Ltd.) was used for measurement.

[0215] <Color flop value>

[0216] The multi-angle spectrophotometer "MA-68II" (trade name, produced by Videojet X-Rite) was used to measure the spectral reflectance of the light irradiated on the coating film at an angle of 45 degrees, with respect to the light receiving angle of regular reflection light being 15 degrees and 45 degrees, and the Y value (Y15 and Y45, respectively) in the XYZ color system calculated from the spectral reflectance was calculated. The calculation was performed using the following formula.

[0217] FF value = 2×(Y15-Y45) / (Y15+Y45)

[0218] <Restorability>

[0219] The multilayer coating surface of each test plate obtained as described above was polished with #600 waterproof sandpaper and #1200 waterproof sandpaper in a circle with a radius of about 2 cm until the surface of the electrodeposition coating film at the center of the circle was exposed.

[0220] Next, a coating leveling agent "Retan PG Eco Boca Leveling Agent" (trade name, manufactured by Kansai Paint Co., Ltd., an organic solvent-based coating composition) was applied by air spraying to a thickness of 3 μm in a circle with a radius of about 15 cm centered on the polished portion, and allowed to stand for 1 minute.

[0221] Next, "Retan PGHybrid Eco 531white Base" (trade name, manufactured by Kansai Paint Co., Ltd., a hydroxyl / isocyanate curable organic solvent-based coating composition) was applied by air spray to a thickness of 40 μm in a circle with a radius of about 10 cm centered on the polished portion, and allowed to stand for 5 minutes.

[0222] Next, "Retan PGHybrid Eco 832 Silky Flash M Base" (trade name, manufactured by Kansai Paint Co., Ltd., a hydroxyl / isocyanate curable organic solvent-based coating composition) was applied by air spray to a thickness of 1 μm in a circle with a radius of about 15 cm centered on the polished portion, and allowed to stand for 2 minutes.

[0223] Next, "Retan PGEco HS Clear" (trade name, manufactured by Kansai Paint Co., Ltd., a hydroxyl / isocyanate-curable organic solvent-based coating composition) was applied by air spray in a circle with a radius of about 20 cm centered on the polished portion to a thickness of 40 μm, and then allowed to stand for 5 minutes. The repairability was then evaluated by heating at 60°C for 8 minutes using a hot air circulation drying oven.

[0224] The appearance of the portion where the coating film was removed by grinding and the portion where the coating film was not removed by grinding were evaluated based on the following criteria: ◎ and ○ indicate passing.

[0225] ⊚: No difference was observed between the portion where the coating film was removed by grinding and the portion where the coating film was not removed by grinding.

[0226] ○: There is a slight difference between the portion where the coating film is removed by grinding and the portion where the coating film is not removed by grinding, but there is no problem in practical use.

[0227] ×: There is a clear difference between the portion where the coating film is removed by grinding and the portion where the coating film is not removed by grinding.

[0228] Table 3

[0229]

[0230] Table 4

[0231]

[0232] From the above results, it can be seen that according to the manufacturing methods of Examples 1 to 9, good results were obtained in terms of brightness, 60° specular gloss, angle-dependent color value and repairability, so that a multilayer coating film with high gloss in highlights, high overall brightness from highlights to shadows, and good repairability can be formed. In addition, due to the high brightness and 60° specular gloss, a multilayer coating film with a white metallic texture can be formed.

[0233] In the production method of Comparative Example 1 in which the film thickness of the base coating film was thin, the brightness of the multilayer coating film decreased.

[0234] In the production method of Comparative Example 2 in which the base coating film had a thicker film thickness, the 60° specular glossiness and the angle-dependent color flop value of the multilayer coating film decreased.

[0235] In the production method of Comparative Example 3 in which the brightness of the base coating film was low, the brightness and the color flop value of the multilayer coating film were reduced.

[0236] In the production method of Comparative Example 4 in which the mixing ratio of the aluminum flake pigment (A) and the titanium oxide (B) in the bright pigment dispersion (Y) was larger than the prescribed range, the multilayer coating film had an excessively large angular flop value and reduced repairability.

[0237] In the production method of Comparative Example 5 in which the mixing ratio of the aluminum flake pigment (A) and the titanium oxide (B) in the bright pigment dispersion (Y) was less than the prescribed range, the angular flop value of the multilayer coating film was reduced.

[0238] In the production method of Comparative Example 6 in which the blending amount of titanium oxide (B) in the bright pigment dispersion (Y) was larger than the prescribed range, the repairability of the multilayer coating film was reduced.

[0239] In the production method of Comparative Example 7 in which the blending amount of titanium oxide (B) in the bright pigment dispersion (Y) was less than the prescribed range, the angular flop value of the multilayer coating film was reduced.

[0240] In the production method of Comparative Example 8 in which the film thickness of the bright coating film was large, the brightness of the multilayer coating film was low, the 60° specular glossiness and the angle-dependent color value were too large, and the repairability was reduced.

[0241] Although the embodiments and examples of the present invention have been specifically described above, the present invention is not limited to the above-described embodiments, and various modifications can be made based on the technical idea of ​​the present invention.

[0242] For example, the configurations, methods, processes, shapes, materials, and numerical values ​​mentioned in the above-mentioned embodiments and examples are merely examples, and different configurations, methods, processes, shapes, materials, and numerical values ​​may be used as needed.

[0243] Furthermore, the configurations, methods, steps, shapes, materials, numerical values, and the like of the above-described embodiments may be combined with one another without departing from the gist of the present invention.

[0244] This application is made based on the Japanese patent application (Japanese Patent Application No. 2022-079518) filed on May 13, 2022, and its contents are cited here as reference.

Claims

1. A method for producing a multilayer coating film, comprising the following steps (1) to (4): (1) directly applying the base coating (X) to the electrodeposition coating film to form a base coating film having a dry film thickness of 20 to 35 μm and a brightness L*45 of 85 to 95; (2) applying the bright pigment dispersion (Y) on the base coating film formed in step (1) to form a bright coating film having a dry film thickness of 0.01 to 1.0 μm; (3) applying a two-component clear coating (Z) containing a hydroxyl group-containing acrylic resin and a polyisocyanate compound on the bright coating film formed in step (2) to form a clear coating film; and (4) by heating the uncured base coating film, the uncured bright coating film and the uncured clear coating film formed in the steps (1) to (3), so that the three coating films are cured simultaneously; The bright pigment dispersion (Y) contains aluminum flake pigment (A), titanium oxide (B), hydroxyl-containing acrylic resin (C), viscosity modifier (D) and water. The content of the titanium oxide (B) is 10 to 20% by mass in the total solid content of the bright pigment dispersion (Y). The mixing ratio of the aluminum flake pigment (A) and the titanium oxide (B) is 0.8 to 1.2 in terms of the mass ratio of the aluminum flake pigment (A) to the titanium oxide (B). The multi-layer coating film has a brightness L*45 in the range of 75 to 85, a 60-degree specular gloss in the range of 95 to 105, and a color flop value in the range of 0.5 to 0.

7.

2. A multilayer coating film, which comprises an electrodeposition coating film, a base coating film, a bright coating film and a clear coating film in sequence, The base coating film has a thickness of 20 to 35 μm and a brightness L*45 of 85 to 95. The bright coating film contains aluminum flake pigment (A) and titanium oxide (B) and has a film thickness of 0.01 to 1.0 μm. The content of titanium oxide (B) in the bright coating film is 10 to 20% by mass, and the mass ratio of aluminum flake pigment (A) to titanium oxide (B) is 0.8 to 1.

2. The transparent coating film comprises a cured product of a hydroxyl-containing acrylic resin and a polyisocyanate compound. The multi-layer coating film has a brightness L*45 in the range of 75 to 85, a 60-degree specular gloss in the range of 95 to 105, and a color flop value in the range of 0.5 to 0.7.